Biologically inspired textiles - Abbott, Albert G.; Ellison, M. (CRC Press ; Woodhead, 2008)
Biomimetic materials are those inspired from nature and implemented into new fibre and fabric technologies. Biologically inspired textiles explores the current state of the art in this research arena and examines how biomimetics are increasingly applied to new textile technologies. Part one discusses the principles, production and properties of biomimetics. Chapters include recombinant DNA technologies and their application for protein production, spinning of fibres from protein solutions and structure/function relationships in spider silk. The second part of the book provides a review of the application of biomimetics to a range of textile applications, including the design of clothing and self cleaning textiles. Written by a distinguished team of international authors, Biologically inspired textiles is a valuable reference for textile technologists, fibre scientists, textile manufacturers and others in academia. Discusses the principles, production and properties of biomimeticsReviews the application of biomimetics to a range of textile disciplinesChapters explore recombinant DNA technologies, spinning of fibres and structure/function relationships in spider silk.
Keywords: Biomimetics -- Materials.; Materials -- Biotechnology.; Textile fabrics -- Technological innovations.; elektronické knihy; electronic books